Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1093/bjs/znaa008
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes after radioactive 125I seed versus hookwire localization of non-palpable breast cancer: a multicentre randomized clinical trial

Abstract: Background Previous studies have suggested improved efficiency and patient outcomes with 125I seed compared with hookwire localization (HWL) in breast-conserving surgery, but high-level evidence of superior surgical outcomes is lacking. The aim of this multicentre pragmatic RCT was to compare re-excision and positive margin rates after localization using 125I seed or hookwire in women with non-palpable breast cancer. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…Results of this study showed the re‐excision rate of HWL was 18.9% and radioactive seeds 13.9%. This indicates that Magseeds are comparable to these modalities 29 . Results are also comparable to a recent systemic review of 16 studies, which found the overall re‐excision rate was 11.25% 13 …”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Results of this study showed the re‐excision rate of HWL was 18.9% and radioactive seeds 13.9%. This indicates that Magseeds are comparable to these modalities 29 . Results are also comparable to a recent systemic review of 16 studies, which found the overall re‐excision rate was 11.25% 13 …”
Section: Discussionsupporting
confidence: 83%
“…This re‐excision rate is less than the 19.5% overall re‐operation rate following breast conserving surgery published by one of the participating institutions prior to the use of Magnetic technology 27 . Our re‐excision rate is similar to recently published Australian studies, 28,29 including a study comparing the re‐excision rate of HWL and radioactive seeds for non‐palpable breast cancers. Results of this study showed the re‐excision rate of HWL was 18.9% and radioactive seeds 13.9%.…”
Section: Discussionsupporting
confidence: 72%
“…In total, 24 RCTs fulfilled our inclusion criteria and were included in this systematic review and NMAs ( Fig. 1 ) [ 16 , 27 , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] ]. Of the 24 RCTs included in this analysis, almost 40.0% were conducted in European surgical research institutions (37.5%, 9/24).…”
Section: Resultsmentioning
confidence: 99%
“…There was low to moderate risk of bias among the included RCTs: Overall, 10 of the included RCTs had low-risk of bias (41.7%) [ 27 , 42 , 45 , 50 , 51 , 53 , 54 , 57 , 61 , 62 ], 12 of the RCTs included some concerns for bias (60.0%) [ 16 , 24 , 41 , 44 , [47] , [48] , [49] , 52 , 55 , [58] , [59] , [60] ], while 2 RCTs were considered high-risk of bias (10.0%) [ 46 , 56 ]. Risk of bias assessment is illustrated in the Supplementary Appendix 1 .O.…”
Section: Resultsmentioning
confidence: 99%
“…Not all of these, however, are funded, all have advantages and disadvantages, but only radioactive iodine seeds have been shown to be more accurate than hookwires in a randomised trial, thus decreasing re-excision rates. 36 About 30 years ago, it was postulated that delivering chemotherapy upfront before surgery may have a number of advantages over the usual policy of surgery first. This neoadjuvant approach is now offered to 10-20% of patients diagnosed with breast cancer.…”
Section: Treating Breast Cancer: Evolution Of Surgical Managementmentioning
confidence: 99%